Dynamic disproportionate collapse in flat-slab structures - Qian, Kai (2014)
Disproportionate collapse of structures can lead to catastrophic economic loss and casualties, and thus, it is of utmost concern to mitigate the risks of such events. Flat-slab structures are much more vulnerable to disproportionate collapse than moment-frame structures as there are no beams to redistribute the loads initially resisted by the lost column. Moreover, the propagation of punching-shear failure at slab– column connections due to load redistribution may result in the collapse of the entire slab. Thus, increased attentions should be paid toward assessing the disproportionate collapse performance of flat-slab structures. However, to date, limited knowledge exists regarding the risks of disproportionate collapse in flat-slab structures, especially in terms of dynamic tests. For this purpose, a series of one-third-scaled flat-slab substructures were subjected to the simulated sudden-column-removal scenario and the failure mode, acceleration, and displacement responses were presented and discussed. To attain a deeper understanding of the dynamic load–redistribution capacity of flat-slab structures, numerical and parametric analyses were also carried out. The possible load-resisting mechanism (membrane action, postpunching behavior, and flexural strength) of flat-slab structures to mitigate disproportionate collapse is also discussed.